Art historiography and Bild-wissenschaft: new perspectives on some objects by the Venda sculptor, Phutuma Seoka - De Villiers-Human, Suzanne (University of the Free State, 2012)
English: It is argued that the apparatus of western art history has been sharpened by the current media consciousness. Typical art historical tools are self-consciously harnessed in the process of scrutinising objects which resist and expand these methods and theories. The focus is on some objects of Venda polychrome sculpture which “took the South African art world by storm” in the 1980s when these specimens of rural craftsmanship in wood were deemed fit to enter the gallery circuit. An analysis of the Venda sculptors’ religious and social knowledge of the use of patterned decoration on ritual tools in wood, and of performances by firelight of myths of origin with wooden dolls during initiation rituals, informs my alternative interpretation of the modern polychrome sculptures steering away from issues of cross-cultural aesthetics, the dialectic of modernism and traditionalism and post-colonial studies. Rather, I interpret the works as medium-self-conscious objects which extend their own cultural and social agency to communicate more widely to a non-initiate audience which may include visitors to an art museum. This shift of focus from a history of art to a history of media effects an altered perspective on the objects themselves and on the methods used to interpret them.

Afrikaans: Daar word geredeneer dat die gereedskap van die westerse kunsgeskiedenis deur die gangbare sensitiwiteit vir media verskerp is. Tipiese kunshistoriese apparaat word selfbewus ingespan in die proses om objekte te ondersoek wat hierdie metodes en teorieë teensit en uitbrei. Die fokus is op ’n paar Venda polichroom beeldhouwerke wat die “kunswêreld op hol gehad” het gedurende die 1980’s toe hierdie voorbeelde van landelike vakmanskap geskik geag is om kunsgalerye te betree. ’n Ontleding van die Venda beeldhouers se religieuse en sosiale kennis van die gebruik van patroondekorasie op rituele houtvoorwerpe, en van rituele uitvoerings van oorsprongmites met houtpoppe by vuurlig gedurende inisiasiegeleenthede, is ’n bron van my alternatiewe interpretasie van die moderne polichroom beeldhouwerk en beweeg weg van vrae oor kruiskulturele estetika, die dialektiek van modernisme en tradisionalisme en die veld van postkoloniale studie. Dit word eerder as medium-bewuste objekte geïnterpreteer wat hul eie kulturele en sosiale vermoë om wyer te kommunikeer tot ’n nie-geïnisieerde gehoor (wat kunsmuseumbesoekers mag insluit) uitbrei. Hierdie verskuiwing van ’n geskiedenis van kuns na ’n geskiedenis van media het ’n veranderde perspektief ten gevolg op sowel die objekte as op die metodes waardeur dit geïnterpreteer word.
Keywords: Historiography; Art history; Bildwissenschaft; Seoka, Phutuma